Enhancing Proton Exchange Membrane Fuel Cell (PEMFC) Performance through Optimized Design of Parallel Channel Bipolar Plates - Moh Nurkhamal; Vika Rizkia; Vina Nanda Garjati; Radhi Maladzi (Recent in Engineering Science and Technology, 2025)
In this modern era, the demand for efficient and environmentally friendly energy sources is increasing. One technology with significant potential to meet this demand is the Proton Exchange Membrane Fuel Cell (PEMFC). This study aims to investigate the influence of channel width and depth variations in parallel bipolar plate designs on PEMFC performance. Computational Fluid Dynamics (CFD) was employed to analyze hydrogen flow distribution and pressure across various design variations. The results demonstrate that channel width and depth significantly affect pressure distribution and flow velocity, which in turn influence the efficiency of the PEMFC system. Increasing channel width generally reduces maximum pressure, while deeper channels help to distribute pressure more evenly across the bipolar plate. Optimized channel width and depth can enhance PEMFC operational performance by reducing pressure drop and promoting uniform flow distribution.